A concept of musical and dance movement against drugs for Indonesian young generation - Maria Etika Tara; Bulan Nauli Rivinandya Juhara (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2019)
As time goes by, drugs abuse and trafficking has been spreading across the globe including Indonesia. With influence from various factors and the increasingly easier access to such products, many adolescents in Indonesia fall into drugs and develop an addiction. Based on this cause, we created an anti drugs themed performance concept which consists of dance and music. We chose dance and music as a way of delivering their message because through music and dance the heavy topic would feel lighter and easier to understand. In addition, dance and music are widely accepted as a form of non verbal communication. The dance that will be showcased is a contemporary dance where the movements tells the story of a drug user and the negative impacts he will experience. Similarly, the song that will be performed would convey a message about the dangers of drug use. We have received some references from the National Narcotics Board (BNN) to hold an event at one of Jakarta's schools that are prone to drugs. Hope that the work of this event concept can assist those who also feel concerned about the future of Indonesian adolescents related to the dangers of drug use.